Empowerment Of Community (Health And Family Cadres) In Early Detection Of High Risk Pregnant Mothers As A Prevention Of Pregnancy Complications - Deasy Irawati (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Purpose of activity: Increase community participation in early detection of risks in pregnant women to avoid complications in pregnancy. Methods of service: Workshop to support cadres in identifying high-risk pregnancies, home visits by cadres to pregnant women to identify and find high-risk pregnant women and inform health workers, provision of ANC services, and health education to high-risk pregnant women by health workers. Results: The ISBN module, HAKI increased health cadres' knowledge of early detection of high-risk pregnancies by 100% in the poor category before receiving the information, and by 100% in the good category after receiving the information, coverage of high-risk pregnancies found by health cadres, and reported to the village midwife by 100%, knowledge of mothers and families regarding early detection of high-risk pregnancies before receiving the information by 6 people (66.7%) in the poor category, 3 people (33.3) in the medium category. After receiving the information, 9 persons (100%) were in a good category. Conclusion: Community (cadres and families) participation in the early detection of high-risk pregnant women has increased.